Channelling The Nigeria’s Foreign Exchange Reserves into Alternative Investment Outlets: A Critical Analysis - Abiola, Asimiyu Gbolagade; Adebayo, Francis Ojo (International Journal of Economics and Financial Issues, 2013)
In recent years, impressive price of crude oil has stimulated the accumulation of foreign exchange reserves in Nigeria. However, observers have expressed fears about the channels of utilisation of the reserves, especially to other alternatives investment outlets. This paper examines the cost-effective propositions of the foreign reserves in Nigeria, and considers alternative investment channels. The study uses data from publications of the Central Bank of Nigeria (CBN), Statistical Bulletin, Annual Reports and Statement of Accounts. It adopts the theory of demand for international reserves based on three motive notably transaction, precautionary and mercantilist. The study among others finds that Nigeria foreign reserve is adequate. The level of reserves to import satisfies the international benchmark etc. The study recommends among others the need to split foreign reserves into four portfolios. The liquidity portfolio, long-term portfolio or investment portfolio, immunization portfolio, and the petroleum fund buffer portfolio or sovereign wealth fund. Keywords: Foreign exchange reserve; investment outlet; gross domestic product JEL Classifications: F31; P45 <!–[endif] –>